The microbial growth potential of antiscalants used in seawater desalination. (15th April 2023) - Hasanin, Ghadeer; Mosquera, Ana Maria; Emwas, Abdul-Hamid; Altmann, Thomas; Das, Ratul; Buijs, Paulus J.; Vrouwenvelder, Johannes S.; Gonzalez-Gil, Graciela
Highlights: The seawater bacterial growth potential of eight diverse antiscalants is presented. Phosphonate-based antiscalants promoted a broad range of seawater bacterial growth. Phosphonate antiscalant without orthophosphates did not promote bacterial growth. Biopolymers and polymers-based antiscalants promoted limited bacterial growth. Antiscalants NMR fingerprinting contributes to an informed selection of antiscalants. Abstract: 20 years since the first report on the biofouling potential of chemicals used for scale control, still, antiscalants with high bacterial growth potential are used in practice. Evaluating the bacterial growth potential of commercially available antiscalants is therefore essential for a rational selection of these chemicals. Previous antiscalant growth potential tests were conducted in drinking water or seawater inoculated with model bacterial species which do not represent natural bacterial communities. To reflect better on the conditions of desalination systems, we investigated the bacterial growth potential of eight different antiscalants in natural seawater and an autochthonous bacterial population as inoculum. The antiscalants differed strongly in their bacterial growth potential varying from ≤ 1 to 6 μg easily biodegradable C equivalents/mg antiscalant. The six phosphonate-based antiscalants investigated showed a broad range of growth potential, which depended on their chemical composition, whilst the biopolymer and the synthetic carboxylated polymers-based antiscalants showed limited or no significant bacterial growth. Moreover, nuclear magnetic resonance (NMR) scans enabled antiscalant fingerprinting, identifying components and contaminants, providing a rapid and sensitive characterization, and opening opportunities for rational selection of antiscalants for biofouling control. Graphical abstract: Image, graphical abstract